Tubaric Pregnancy Combined an Intrauterine Pregnancy with Placental Abruption: A Rare Clinical Case in Emergency and Review of the Literature (British Journal of Multidisciplinary and Advanced Studies, 2025)
A tubaric pregnancy combined with an intrauterine pregnancy with placental abruption is an extremely rare and very high-risk condition that requires urgent and highly specialized medical care. The coexistence of these two conditions makes the diagnosis difficult, because symptoms can often overlap and there is a high risk of bleeding, which is why it requires a high index of suspicion. Risk factors can be multiple but most frequently involve the use of assisted reproductive technologies. Treatment options, from observation to surgery, must be carefully selected based on the clinical situation and management must aim at improving the obstetric outcome for a viable intrauterine pregnancy. Surgical treatment is aimed at removing the tubaric pregnancy, controlling the bleeding and preserving the intrauterine pregnancy. For patients with unstable hemodynamics or with any signs indicating rupture of an ectopic pregnancy, emergency surgery is always strongly recommended. Coexisting placental abruption in an intrauterine pregnancy, if it is partial as in the reported clinical case, may reabsorb spontaneously. The maternal and intrauterine fetal prognosis depends on early diagnosis and fetal survival is good if diagnosis is timely, treatment is appropriate and strict follow-up is performed. At this stage, close monitoring in hospitalization is required and emotional support is essential because the situation is extremely stressful for the patient.